Advancing the repurposing of ivermectin for malaria - Chaccour, Carlos; Rabinovich, N Regina (The Lancet (British edition), 2019)
There is ever-increasing anticipation for the potential of mass drug administration of endectocides (also known as systemic insecticides) to reduce malaria transmission, with ivermectin emerging as the most likely first-in-class endectocide.1 More than half of the 46 papers published on this subject in the past decade appeared in the past 2 years. 23 projects are registered in the MESA Track database, of which seven are active today; and, more importantly, trial mapping by the Malaria Ivermectin Roadmap2 shows that abundant new evidence on the topic will be available by 2020. After achieving remarkable advances from 2000 to 2015, the global fight against malaria has stalled.3 Beyond funding and access gaps, residual transmission—driven by mosquito behavioural adaptations that allow avoidance of home-based insecticides—has become a key liability for vector control, and challenges achievement of the global goals set forth by WHO.4 Ivermectin lays the path for a whole new concept: drug-based vector control.5,6 Ivermectin, or indeed any effective endectocide, could be administered to eligible members of the at-risk community as a complementary tool for vector control. Eligible village residents in the control and intervention groups received a single 150–200 μg/kg dose of ivermectin plus 400 mg of albendazole, but those in the intervention group received five additional 3-weekly doses of ivermectin alone, with mass drug administration coverage of 70–75% across the 18-week intervention period.